The Effect of Proprioceptive Neuromuscular Facilitation Stretching Program on Improving Vertical Jump Strength in Volleyball Smash Performance - Faizal Rizky Kurniawan; Yulius Agung Saputro (Universitas Riau, 2025)
This study aimed to examine the effect of Proprioceptive Neuromuscular Facilitation (PNF) stretching on improving vertical jump performance during smash jumps in volleyball players at SMA Kesatuan Bangsa Yogyakarta. The study employed an experimental method using a one-group pretest–posttest design. The participants were male volleyball players involved in extracurricular activities. The research instrument was a vertical jump test to measure lower limb strength before and after the intervention. The treatment consisted of a structured training program combined with PNF stretching. Data were analyzed using normality tests, homogeneity tests, and a paired sample t-test with a significance level of 0.05. The results showed that PNF stretching had a significant effect on increasing vertical jump performance. Therefore, PNF stretching can be recommended as an effective alternative training method to enhance smash jump performance in high school volleyball players.